2015
DOI: 10.1152/ajpheart.00158.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oral N-acetylcysteine on walking capacity, leg reactive hyperemia, and inflammatory and angiogenic mediators in patients with intermittent claudication

Abstract: . Effects of oral N-acetylcysteine on walking capacity, leg reactive hyperemia, and inflammatory and angiogenic mediators in patients with intermittent claudication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 70 publications
4
14
0
1
Order By: Relevance
“…We have shown that high‐dose oral NAC can increase peripheral antioxidant measures. In agreement with our observations, there have been several reports of increased antioxidant GSH/GSSG ratios with oral NAC therapy . In our study, despite the observed increase in antioxidant capacity (GSH/GSSG and catalase), oral NAC did not appreciably alter peripheral measures of oxidative damage (4‐HNE and MDA).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We have shown that high‐dose oral NAC can increase peripheral antioxidant measures. In agreement with our observations, there have been several reports of increased antioxidant GSH/GSSG ratios with oral NAC therapy . In our study, despite the observed increase in antioxidant capacity (GSH/GSSG and catalase), oral NAC did not appreciably alter peripheral measures of oxidative damage (4‐HNE and MDA).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our observations, there have been several reports of increased antioxidant GSH/GSSG ratios with oral NAC therapy. [33][34][35] In our study, despite the observed increase in antioxidant capacity (GSH/GSSG and catalase), oral NAC did not appreciably alter peripheral measures of oxidative damage (4-HNE and MDA). However, given that these measures were not elevated in patients, we might not expect to see a modulating effect.…”
Section: Discussionmentioning
confidence: 74%
“…Because the molecular mechanisms regulating endothelial dysfunction are likely not isolated to a single pathway, more clinical studies that include molecular measurements are needed. The present study by da Silva et al (9) and the work by Ahimastos et al (1,2) show the value of such experiments in conjunction with clinical outcomes to gain insight into potential mechanisms regulating vascular function. In summary, it will be important to delineate the multiple mechanisms that mediate PAD-related vascular impairments and determine whether they vary by risk factor and patient makeup.…”
supporting
confidence: 55%
“…( 17 ) Circulating miR-126-3p is known to be suppressed in patients or animal models of cerebral ischemic stroke, diabetes, or peripheral arterial disease. ( 17 , 24 , 27 ) Furthermore, oxidative stress might play a role in releasing circulating miR-126-3p as oral treatment with the antioxidant N -acetylcysteine (NAC) was found to prevent the maximal exercise-induced increase of circulating miR-126-3p in patients with intermittent claudication. ( 24 ) Wang et al ( 23 ) reported that miR-126-3p contained in endothelial progenitor cell-derived microvesicles (EPC-MVs) can suppress oxidative stress and promote angiogenesis of endothelial cells via the PI3K/eNOS/NO pathway.…”
Section: Resultsmentioning
confidence: 99%